Análise do desempenho cinemático de um mecanismo planar paralelo sujeito a incertezas - Proenca, Tyago Fylipe Vieira (2019)
Parallel mechanisms are unavoidably subjected to uncertainties. These uncertainties produce a small variation of link lengths and joint position. Therefore, this contribution aims at analyzing the effect of these uncertainties on the kinematic performance of the mechanism. Initially, the complete kinematic model of the mechanism is formulated by considering the uncertainties that are modeled as random variables. Then, the kinematic performance atlases based on workspace size and kinematic dexterity are analyzed including the uncertainties. Finally, the kinematic accuracy is evaluated for several poses within the workspace showing the correspondent relationship with the kinematic performance atlases.